Game of thrones. The complete seventh season [videorecording (DVD)] - Podeswa, Jeremy; Mylod, Mark; Dinklage, Peter; Headey, Lena; Martin, George R. R. (HBO Home Entertainment, 2017)
Follows the adventures of the powerful families in the kingdom of Westeros that are constantly vying for control of the throne.